Peningkatan Kemampuan Komunikasi dan Penalaran Matematis Siswa Madrasah Aliyah melalui Model Pembelajaran Kooperatif Tipe - Nur Ainun; M. Ikhsan; Said Munzir (Didaktik Matematika, 2015)
Abstract. Communication skills and mathematical reasoning is one of the objectives of the study of mathematics. Communication is defined as the ability to write, read, listen, examine, interpret, and evaluate ideas, symbols, terms, and mathematical information. Mathematical reasoning is a habit when the brain is well developed and consistent will facilitate the mathematical communicate both written and oral. Therefore, the necessary relevant learning models to optimize, improve, and develop communication and mathematical reasoning abilities of students. One of the cooperative learning models is Teams Games Tournament (TGT). The aim of this study to determine: (1) Is the increase in communication and mathematical reasoning abilities that students acquire learning with cooperative learning model TGT better than students who received conventional learning approaches, and (2) What is the attitude of students towards learning mathematics learning gain with cooperative learning model TGT. This research was experimental research design with pretest-posttest control group design. The population in this study was all students of class XI MAN Darussalam Aceh Besar, which consists of five classes. While the sample was composed of two classes of experimental classes and control classes were taken by random sampling. The instrument used to obtain research data communications test and mathematical reasoning ability, and attitude scale questionnaire. The statistical test used for the data mengalisis increase communication skills and mathematical reasoning was two lanes ANOVA test, while the attitude scale questionnaire was calculated based on a percentage. The results showed that the overall improvement of communication and mathematical reasoning abilities that students acquire learning with cooperative learning model Teams Games Tournament better than students who received study with conventional approaches. From the results of student questionnaire concluded that in general the students had the positive attitude towards learning mathematics using cooperative learning model TGT.Key Word: Learning TGT, Communication, Reasoning